2005
DOI: 10.1002/ca.20113
|View full text |Cite
|
Sign up to set email alerts
|

Unusual attachment of the pectoralis minor muscle

Abstract: The authors report a presumably unusual bony attachment of the pectoralis minor muscle in an adult cadaver. The specimen's left pectoralis minor had no attachment to the coracoid process of the scapula but attached directly to the fibrous capsule of the glenohumeral joint. Some have theorized that the coracohumeral ligament represents fibers of the pectoralis minor that attach to this bone in some animals but that has degenerated in man. This case report seems to support this possibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Another variation of rotator interval anatomy that has been described is an insertional anomaly of the pectoralis minor tendon combined with absence of the coracohumeral ligament [13,14]. One radiology review of this entity found this variation in 1.5% of shoulder MR arthrograms [14].…”
Section: Variant Attachment Site Of the Pectoralis Minor Tendonmentioning
confidence: 97%
“…Another variation of rotator interval anatomy that has been described is an insertional anomaly of the pectoralis minor tendon combined with absence of the coracohumeral ligament [13,14]. One radiology review of this entity found this variation in 1.5% of shoulder MR arthrograms [14].…”
Section: Variant Attachment Site Of the Pectoralis Minor Tendonmentioning
confidence: 97%
“…1 Tubbs et al reported that the specimen's left pectoralis minor had no attachment to the coracoid process but attached directly to the fibrous capsule of the glenohumeral joint, in the absence of the coracohumeral ligament. 8 Tugut et al observed a bilateral insertion variation of pectorals minimus (sterno-costo-coracoidian muscle). One of them took origin from the second costal cartilage to the manubrium sterni and the second costochondral joint; afterwards, it became a tendinous structure and divided into 2 on the coracoid process.…”
Section: Discussionmentioning
confidence: 98%
“…5 Actually, these anatomic anomalies are not uncommon 2 and have also been reported by some authors as an incidental finding encountered during cadaveric dissection or surgical procedure. 1,3,4,8,10 However, its clinical significance in shoulder still remains obscure and the role can be debated. Further investigations are warranted to have clear impact on the shoulder function.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors [7,8] consider the coraco-humeral ligament as a post-coracoid extension of the pectoralis minor tendon. According to Testut [2], anatomic variations are the result of abnormal development during the first weeks of embryonic life.…”
Section: Discussionmentioning
confidence: 99%